Amplitudes and Directions of Individual Saccades Can Be Adjusted by Corollary Discharge - Joiner, Wilsaan M. (2010)
There is strong evidence that the brain can use an internally generated copy of motor commands, a corollary discharge, to guide rapid sequential saccades. Much of this evidence comes from the double-step paradigm: after two briefly flashed visual targets have disappeared, the subject makes two sequential saccades to the targets. Recent studies on the monkey revealed that amplitude variations of the first saccade led to compensation by the second saccade, mediated by a corollary discharge. Here, we investigated whether such saccade-by-saccade compensation occurs in humans, and we made three new observations. First, we replicated previous findings from the monkey: following first saccade amplitude variations, the direction of the second saccade compensated for the error. Second, the change in direction of the second saccade followed variations in vertical as well as horizontal first saccades although the compensation following horizontal saccades was significantly more accurate. Third, by examining oblique saccades, we are able to show that first saccade variations are compensated by adjustment in saccade amplitude in addition to direction. Together, our results demonstrate that it is likely that a corollary discharge in humans can be used to adjust both saccade direction and amplitude following variations in individual saccades.